Associations between APOE polymorphisms and seven diseases with cognitive impairment including Alzheimer's disease, frontotemporal dementia, and dementia with Lewy bodies in southeast China. (June 2016) - Chen, Ke-Liang; Sun, Yi-Min; Zhou, Yan; Zhao, Qian-Hua; Ding, Ding; Guo, Qi-Hao
Abstract : Objective: To explore the effect of APOE polymorphisms on patients with cognitive impairments in The Chinese Han population. Materials and methods: A total of 1027 cases with Alzheimer's disease (AD), 40 cases with vascular dementia (VaD), 28 cases with behavioral variant frontotemporal dementia (bvFTD), 54 cases with semantic dementia (SD), 44 cases with dementia with Lewy bodies (DLB), 583 cases with mild cognitive impairment (MCI), and 32 cases with vascular cognitive impairment no dementia (VCIND) were recruited consecutively from memory disorders clinics in Huashan Hospital between January 2010 and December 2014. The 1149 cognitively normal controls were recruited from the community epidemiologic investigations. The APOE genotypes were determined using the TaqMan assay. Results: The distribution of genotype and allele frequencies of APOE differed significantly between control and AD or MCI, with ε4 increasing the risk of AD and MCI in a dose-dependent pattern and ε2 decreasing the risk of AD, but not the risk of MCI. As for VaD, significant differences in the APOE genotype distribution were found compared with the controls. E4/4 increased the risk of VaD and ε4 increased the risk of VCIND in women. The allele distribution differed between bvFTD and controls, but genotype and allele frequencies of APOE did not affect the risk of bvFTD, SD, and DLB. Conclusion: In The Chinese Han population, APOE ε4 increased the risk of AD and MCI in a dose-dependent manner and ε2 decreased the risk of AD as reported previously. APOE ε4 might increase risk in VaD and female patients with VCIND, but no effects of APOE on bvFTD, DLB, and SD were found. Abstract : Supplemental Digital Content is available in the text.